359 An Uncommon Case of Congestive Heart Failure (CHF): Is the Quality of Care Income Driven?. (11th January 2018) - Livingston, Stephanie; Abdallah, Adel; Wilson, Matthew; Pearlman, Eugene
Abstract: Objectives: Amyloidosis is an uncommon cause of CHF, and it is now possible to define its etiology at the molecular level. We present the case of a 68-year-old African-American male veteran who presented to the emergency department with dyspnea and anasarca. An ECHO study indicated severe ventricular dysfunction (EF 30%) and identified changes ("speckling") suspicious for the presence of amyloid material. The patient was unaware of any family history of cardiomyopathy. Methods: Abdominal fat pad and endomyocardial biopsy were focally positive for apple green birefringence using polarized light following Congo red staining. Molecular studies (ARUP, Salt Lake City, UT) indicated homozygosity for a mutation in the transthyretin (TTR) gene reported to have a frequency of 3%-4% in the African-American population in the US but to be non-detectable in the Caucasian population. Assay using HPLC-MS on the endomyocardial biopsy material (Mayo Medical Labs, Rochester, MN) confirmed TTR deposition. Results: Presently cardiac transplantation is the only treatment option available for TTR-mutation related cardiac amyloidosis. The patient however was deemed an unsuitable candidate for transplant in part because, as stated, "his caregiver situation [was] difficult; [he was] separated from [his] wife, and she and [their] children work and cannot afford to stop working to be with him." This citation raises the question of whether eligibility for transplant is determined, at least, in part, by the income of prospective recipient being sufficiently high to afford the presence of an on-site caregiver. Conclusion: This case raises some fundamental issues of transplantation criteria in the US system of medical care.